Analisis Tingkat Kelulusan Welder Qualification Test Berdasarkan AWS D1.1/D1.1M:2020: Analysis of Pass Rates for the Welder Qualification Test Based on AWS D1.1/D1.1M:2020 - Adhe Aryswan; Rio Rahmad Guntur; Ari Wibowo; Nurman Pamungkas (Universitas Pendidikan Ganesha, 2026)
The welder qualification process is pivotal to ensuring quality welding in fabrication industries. This study presents the outcomes of a welder qualification test conducted from February 16 to 17, 2023, involving 151 participants across seven batches. Utilizing the AWS D1.1/D1.1M:2020 standard, participants underwent visual inspection to assess welding proficiency. Results revealed that 141 welders successfully met qualification criteria, while 10 encountered failures primarily due to fast travel speeds and high ampere settings leading to visible defects. The qualification process showcased a 90% success rate on the first day and 100% success on the second day. Grades A, B, and C were employed to assess visual inspection outcomes, with most participants achieving grades A and B. Overall, the study emphasizes the importance of meticulous adherence to welding parameters and procedures to ensure successful qualification outcomes. Addressing identified areas of improvement, particularly regarding welding parameters, is crucial for enhancing the effectiveness of future qualification processes and nurturing a skilled workforce in alignment with industry standards.